IMPROVING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT BY USING RAINBOW CARD IN FEEDBACK STRATEGY - Rita Harisma; Masitoh Nasution (Jurnal Serunai Bahasa Inggris, 2020)
This research was aimed to improving students’ reading comprehension of Descriptive text by using Rainbow Card in feedback strategy. The subject of the study were the students of SMP Swasta AL-Hikmah Medan Academic Year  2019/2020. The research of this study was conducted by using classroom action research. The data used in this research were qualitative and quantitative data. The result of this research showed that there were increasing of students’ reading comprehension. The mean of the pre-test was 44.6, in cycle one was 64.6, in cycle two was 80, it indicated that the scores and the mean in cycle two was better than the first one. In the pre-test of cycle one, there were not students who got point 70. In the post test of cycle one the students who got point 70 or more there were 26 of students (52%), it means that there were an increasing about 52%. The post-test of cycle two, the students who got point 70 or more there were 42 students (84%) and the increasing was about 32%. The scores of observation sheet were 4 (very good). The students paid attention and also felt spirit in doing the reading test, and students more interested, enjoyed, and enthusiastic in doing the task by using feedback strategy.Keywords: Reading Comprehension, Descriptive Text, Rainbow Card, Feedback Strategy